Effect of Selected Pretreatments on Convective Drying Process of Blueberries (Var. O Neil) - Lemus-Mondaca, R (2012)
The effects of different pretreatments on the convective drying kinetics of blueberries (var. O Neil) at 70 °C were investigated. The sodium hydroxide, enzymatic, microwaves, and high hydrostatic pressure pretreatments were applied and compared with control samples (non-pretreated). In order to simulate experimental drying data, the following mathematical models were selected: logarithmic, two terms, modified Henderson-Pabis, Midilli-Kucuk, and Weibull. Fick s second law of diffusion was applied to determine the water diffusion coefficient for all the treatments. All pretreatments decreased significantly the drying time of the control samples. High hydrostatic pressures together with microwave pretreatments presented lower drying times than non-pretreated samples. Moreover, based on statistical test results, Weibull and modified Henderson-Pabis models presented the best fit for the experimental drying curves. Thus, both models can be satisfactorily applied to estimate the drying time of blueberries as well as to evaluate the effects of different pretreatments on fruit drying rates. © 2011 Springer Science+Business Media, LLC.